Irrationality rings!: Experimental evidence on mobile tariff choices - Anne-Kathrin Barth; Julia Graf (International Telecommunications Society (ITS), 2012)
This paper investigates why consumers choose calling plans that are not always cost-minimizing. Our approach is twofold: we account for general difficultiesfacing a tariff choice, as well as for biased preferences. We provide evidence froman experiment among German university students and staff, finding that participants are often not aware of their actual consumption. In line with the findings on at-rate biases, respondents systematically overestimate their consumption. On the other hand, they are generally able and willing to detect optimal tariffs. Furthermore, with increasing usage level, consumers' performance improves. However, some participants hold preferences for certain tariff forms, seducing them to choose cost-dominated offers. In our setup, we find that respondents prefer tariffs involving subsidies or hire-purchase options for handsets over contracts with buy now options.
Keywords: 330; Behavioral Economics; Mobile phone tariffs; Handset subsidy; Hirepurchase of device